Current Recommendations on Diagnosis and Management of Right-Sided Diverticulitis - Dana A. Telem; Kerri E. Buch; Scott Q. Nguyen; Edward H. Chin; Kaare J. Weber; Celia M. Divino (Gastroenterology Research and Practice)
We present the case of a 52-year-old female with recurrent symptomatic ascending colon diverticulitis who ultimately underwent elective laparoscopic right hemicolectomy. The following is a case report and literature review pertaining to right colonic diverticular disease.